Tinbergen and Theil Meet Nash: Controllability in Policy Games - Giovanni Di Bartolomeo; Nicola Acocella (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper generalizes the classical theory of economic policy to a static LQ-strategic context between n players. We show how this generalized version of controllability can profitably be used to deal with policy ineffectiveness issues and Nash equilibrium existence.
Keywords: C72; E52; E61; 330; Policy games; policy ineffectiveness; static controllability; Nash equilibrium existence; Nash-Gleichgewicht; Wirtschaftspolitik; Theorie